Laboulaye et Kachenovsky et la fabrique du droit international : voyages, réseaux, circulation des savoirs juridiques - Raphaël Cahen (Clio@Themis)
Laboulaye (1811-1883) and Kachenovsky (1827-1872) both travelled around Europe as travelling lawyers in the years 1840-1870. They forged networks and participated in the circulation of knowledges by playing the role of intermediary between international lawyers during the making of “global” international law in the years preceding the founding of the Institut de Droit International. Through unpublished archives, this article sheds light on the geography of the travels of international lawyers as well as the particular role of Laboulaye as a Parisian hub for traveling lawyers.